PENERAPAN MODEL POPULASI KONTINU PADA PERHITUNGAN PROYEKSI PENDUDUK DI INDONESIA (STUDI KASUS: PROVINSI JAWA TIMUR) - ANGGREINI, DEWI (E-Jurnal Matematika, 2020)
The population data in Indonesia that is closest to the actual condition is only the data from the population census conducted by the Central Statistics Agency (BPS). The calculation of population projections in BPS throughout Indonesia uses the component method to see the projection of the population at the provincial level while the district level uses the geometric method with the assumption that the population will begin to increase geometrically with a basic reference for calculating compound interest. This study aims to determine population projections in the province of East Java using exponential and logistical models based on growth rates and carrying capacity. The data used in this study is secondary data, namely the population of the Central Statistics Agency (BPS) of East Java Province in 2012-2019. The research method used is to determine the research subject, collect data, analyze data and draw conclusions. The results of this research are the carrying capacity value of East Java Province of 43,997,165.5 and the logistic model population growth rate of 0.05111. The conclusion of this research is that the most accurate model for estimating the population of East Java is the V logistic model because it has the smallest Mean Absolute Percentage Error (MAPE) value. This research is expected to be useful for users of population data in calculating future population projections